O teste de Painlevé e a integrabilidade do modelo generalizado de sine-Gordon - Mota, Leonides da Rocha (2014)
In this work the integrability of the generalized sine-Gordon model (GsG) is examined in the context of the Painlevé test for partial di erential equations (PDEs). We show that the (GsG) model possesses certain submodels such as the double sine-Gordon (DsG), Bukhvostov-Lipatov (BL) and the integrable sine-Gordon models. The BL model possesses some integrable directions in the eld space. Moreover, we classify the kink type solutions of the (GsG) model through the highest weight representations of the underlying sl(3) Lie algebra, and we show that these masses belong to certain multiplets in that representation scheme. We discussed the integrable defocusing NLS model and study the collision of two dark solitons, in particular we study the phase shift after their collision.